Squishy and Crunchy Invasive Invertebrates: Environmental DNA Is Not Shed Equally - Emily Rose Lancaster; Erin Katherine Grey; Damian Coman Brady; Markus Frederich (Environmental DNA)
ABSTRACT Environmental DNA (eDNA) detection can be a powerful approach to detect organisms in low abundance and can be crucial for early invasive species detection. Despite its potential, the body plan diversity of invertebrates can pose significant challenges, notably arthropods with exoskeletons that may have low eDNA shedding rates. In this study, we validated nine single‐species quantitative PCR assays targeting invasive and nuisance species representing various body plans in the Gulf of Maine, an area of rapid ocean warming. Combining visual surveys and molecular analyses in a two‐year eDNA time series, we successfully detected eight of nine target species with qPCR. Of the soft‐bodied, “squishy” species, four of five exhibited eDNA detection consistent with visual abundances. Of species with an exoskeleton or shell (crunchy), three of four species were not detected consistently in accordance with visual abundance. Our findings demonstrate the effectiveness of eDNA for early invasive species detection but emphasize the need for long‐term field and laboratory validation, informed by species' bauplan. It is imperative to recognize that while eDNA is a valuable tool, its applicability varies across taxa. Therefore, interpreting eDNA results requires careful consideration of its limitations and the specific characteristics of the target organisms.